Spectral optical coherence tomography for nondestructive examinations - Targowski, Piotr; Bajraszewski, Tomasz; Gorczyńska, Iwona; Góra, Michalina; Szkulmowska, Anna; Szkulmowski, Maciej; Wojtkowski, Maciej; Kałużny, Jakub J.; Kałużny, Bartłomiej J.; Kowalczyk, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
An overview of the spectral optical coherence tomography which is the alternative to the traditional Time domain version is given. Examples of applications in ophthalmology as well as in art preservation are presented.
Optica Applicata, Vol. 36, 2006, nr 4, s. 609-619
Keywords: optyka; spectral optical coherence tomography; ophthalmic imaging; nondestructive testing